Joining Of Alumina-Based Composite To 6061 Aluminum Alloy By Friction Welding - Safarzadeh, Marjan (2014)
The present research is aimed at evaluating the feasibility of using the friction welding of mullite and Alumina-Mullite composite with 6061 Alalloy, and subsequently determining their microstructural and mechanical properties. During the process, friction force (1000 bar) and friction time (30 Sec) were held constant while the rotational speed was varied. Ceramic rods aluminium rods were machined down to get the require dimension and then polished. Sintering behaviour of ceramic samples were investigated. It was concluded that the mullite rods didn't join to 6061 Al-alloy due to the low fracture toughness of the mullite. Thus, fracture toughness was improved through the composite of Alumina-Mullite. Welding process was carried out under two different rotational speeds (1250 and 1800rpm) and the effect of increasing rotational speed on microstructure, microhardness and mechanical properties of Alumina-Mullite composite/6061 Al-alloy joined was evaluated. It was observed that a good microstructure with higher mechanical properties (microhardness and bending strength) were achieved from the joining of Alumina-Mullite composite with 6061 Al-alloy at higher rotational speed (1800 rpm). The mechanisms of failure at the fracture surfaces revealed different feature at different speed. At the higher speed dimple and ductile formed which implies the plastic deformation.